Modernization of Eco-friendly Blacksmith Furnace to Fabricate Farms Equipment - Yudha Venditias; Yudhanto Ferriawan; Wisnujati Andika; Jamir Mohd Ridzuan Mohd; Warisaura Angge D. (E3S Web of Conferences)
Blacksmiths manufacture farm equipment that still uses conventional systems in their production. The fabrication process goes through the heating stage of steel to a temperature of 850°C as the primary raw material (carbon steel). Heating aims to make the steel easy to shape into farm tools. Conventional furnace designs, such as those at blacksmiths in the Pandak area, Bantul, still use an open system, causing air pollution around the workplace. This research modernizes a blacksmith furnace for iron with multi-air flow and dust filtration systems. Total dust testing uses SNI 7119-3:2017 standards. The results were that the burning stove has three variations of airflow, which can be adjusted to the type of work to save wood charcoal fuel by around 30%. A combustion furnace with an ash filtration system can minimize pollutant particles around the work environment from 3.99 mg/m3 to 0.024 mg/m3. Modernization of furnaces has reduced air pollution by up to 99%.